Перспективи застосування VR та AR навчання у підготовці біомедичних інженерів - Посохова, К. А. (ХНУРЕ, 2024)
Education of students of various professions mostly depends on distance learning, which can affect the quality of knowledge of future specialists. Practice is especially necessary for students whose work involves risk and the possibility of harming themselves or other people. These technologies are also important for familiarizing personnel and workers with the use of equipment and systems that require special accuracy and knowledge of the operation of devices. Simulating real scenarios, VR technology provides a safe space for future specialists to practice, learn and improve their skills without the risk of potential danger.
Keywords: біомедицина; підготовка біомедичних інженерів